Electronic Medical Records in Increasing User Satisfaction: Literature Review - Suwarti, Sri; Enny Rachmani; Eti Rimawati (Management Analysis Journal, 2025)
The integration of Electronic Medical Records (EMR) into healthcare systems promises significant enhancements in service quality and patient satisfaction. This study systematically reviews literature to assess the impacts of EMR implementation on healthcare efficacy and error reduction. EMRs are pivotal in transforming medical record-keeping by digitizing patient information, thereby facilitating swift access to patient histories, diagnostic data, and treatment plans. This not only assists healthcare professionals in making accurate clinical decisions but also mitigates the risks of allergic reactions and drug duplications. Furthermore, EMRs have been instrumental in reducing the administrative burdens on healthcare providers, streamlining workflows, and decreasing the likelihood of errors, which traditionally plagued paper-based systems. By enhancing the efficiency of the healthcare process, EMRs contribute directly to improved patient outcomes and satisfaction. The review explores diverse methodologies and findings from various studies, highlighting the nuanced benefits of EMRs, including their role in enhancing communication between providers and patients. The study also considers challenges in EMR implementation, such as initial costs and the need for training. Overall, the evidence strongly supports that EMRs are a cornerstone for advancing healthcare quality and patient care experiences. This paper aims to provide a comprehensive overview of the current state of EMR utilization, offering insights for future research and implementation strategies to optimize healthcare services.